Strategies for Developing Children's Interest in Learning at TK Negeri Bangli - Dewa Ayu Anom Krismayanti; Komang Sri Anggreni Putri; Tria Ariani, Nyoman Wiraadi (International Journal of Instructions and Language Studies, 2024)
This qualitative study explores effective strategies for developing children's interest in learning at Bangli State Kindergarten. Through interviews with teachers and parents, the research identifies various strategies that foster children's learning engag ement. The findings reveal that interactive learning methods, including games and creative activities, significantly enhance children's interest by making learning enjoyable and encouraging active participation. Moreover, the study highlights the importance of an engaging classroom environment, characterized by diverse decorations, in stimulating children's curiosity and interest in the lessons. The involvement of parents also emerges as a crucial factor in enhancing children's learning motivation. These insights emphasize the need for a collaborative approach among educators and parents to create a supportive and stimulating learning atmosphere for young children.